ANALISIS PELAKSANAAN SISTEM PENCATATAN DAN PELAPORAN PUSKESMAS (SP3) DI PUSKESMAS PANAWANGAN - Lestary, Farhah Dheya; Kurniasih, Dewi Lena Suryani (Politeknik Kesehatan Kemenkes Malang, 2023)
Background: The Puskesmas Recording and Reporting System (SP3) is a comprehensive recording and reporting activity based on the concept of a health center's working area and useful in supporting health center management. Through SP3, health centers are required to record activities and report regularly to the District Health Office. Based on the initial survey, Puskesmas Panawangan has used an application or website in the reporting section, but the recording section is not yet computerized, resulting in officers having to do the work twice. The health center has facilitated infrastructure but has not fully maximized it. Some officers at the Puskesmas have also not attended SP3 training. The purpose of the study was to determine the implementation of the Puskesmas Recording and Reporting System (SP3) at the Panawangan Health Center, Ciamis Regency.Subjects and Method: Qualitative research with a phenomenological approach. The research was conducted at the Panawangan Health Center in Ciamis Regency. The research subjects consisted of 1 key informant, 5 main informants, and 1 supporting informant. The research instruments used were interview guidelines, observation sheets, cell phones for recording, notebooks, and stationery. Data collection was done through interviews and observation.Results: This There is someone who manages SP3, but there are no medical record graduates, and additional staff are needed for the nutrition program and Pustu. Not all staff have attended SP3 training. The recording and reporting system at Panawangan Health Center has not used a guidebook, or there is no guidebook. Computer facilities are still lacking, so in recording and reporting health centers, officers use privately owned facilities. Internet services are available, but sometimes there are obstacles.Conclusion: The recording and reporting system at Panawangan Health Center has been implemented, and the submission of SP3 reports to the District Health Office has also been carried out on time.